2003
DOI: 10.1183/09031936.03.00402403
|View full text |Cite
|
Sign up to set email alerts
|

Elderly humans exposed to concentrated air pollution particles have decreased heart rate variability

Abstract: Air pollution particles are thought to kill w500,000 people worldwide each year. The population most at risk appears to be elderly people with respiratory and cardiovascular disease. As yet, no commonly accepted mechanism has been proposed which can explain the cause of these deaths.Heart rate variability (HRV) was assessed in healthy elderly adults between the ages of 60 and 80 who were exposed twice for 2 h: once to clean air and once to concentrated ambient air pollution particles (CAPS). Changes in HRV wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

20
157
5
8

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 274 publications
(193 citation statements)
references
References 30 publications
20
157
5
8
Order By: Relevance
“…This was observed as an increase in pulse rate. This is similar with the findings of Devlin et al, (2003) who reported that acute particulate matter exposure is capable of increasing Heart Rate Variability (HRV).…”
Section: Resultssupporting
confidence: 82%
“…This was observed as an increase in pulse rate. This is similar with the findings of Devlin et al, (2003) who reported that acute particulate matter exposure is capable of increasing Heart Rate Variability (HRV).…”
Section: Resultssupporting
confidence: 82%
“…The rising death rate due to air pollution particularly indoor has been supported by Smith et al [10]. Indoor pollution is a repercussion but due to more time spend indoor (> 80%), especially by elders and small children, health problems are found in enhanced proportion in these vulnerable age groups by Devlin et al [11].…”
Section: Resultsmentioning
confidence: 87%
“…The rising death rate due to air pollution particularly indoor has been supported by Smith et al [10]. Indoor pollution is a repercussion but due to more time spend indoor (> 80%), especially by elders and small children, health problems are found in enhanced proportion in these vulnerable age groups by Devlin et al [11].Symptoms of health discomfort were found more (23%) due to indoor pollution than outdoor (9%) [11]. Growing trend of personal transport mode in general has raised air pollution levels to alarming levels in India and it is related to International Journal of Environmental Science and Development, Vol.…”
mentioning
confidence: 88%
“…Evidence suggests that increased PM concentrations mainly affect the cardiovascular and respiratory systems (Peters et al, 1997a(Peters et al, , 1999Gold et al, 2000;Ibald-Mulli et al, 2001;Brook et al, 2002;Devlin et al, 2003;Schulz et al, 2005) and are especially associated with increased cardiovascular hospital admissions (Schwartz, 1999;Zanobetti et al, 2000;Le Tertre et al, 2002;D'Ippoliti et al, 2003;von Klot et al, 2005;Dominici et al, 2006) or increased cardiovascular mortality (Clancy et al, 2002;Forastiere et al, 2005;Zeka et al, 2005;Ostro et al, 2006). The physical or chemical particle properties (e.g.…”
Section: Introductionmentioning
confidence: 99%